Transferability of nuclear microsatellite markers to the atmospheric bromeliads Tillandsia recurvata and T. aeranthos (Bromeliaceae) - Chaves, Cleber Juliano Neves [UNESP]; Aoki-Gonçalves, Felipe [UNESP]; Leal, Bárbara Simões Santos [UNESP]; Rossatto, Davi Rodrigo [UNESP]; Palma-Silva, Clarisse [UNESP] (Springer Nature, 2018)
The genus Tillandsia L. is the most diversified genus of Bromeliaceae and represents one of the most specialized cases of vascular epiphytism: the ‘atmospheric bromeliads.’ Such great diversity and ecological specialization make it an interesting model for evolutionary and population genetics studies. Here we report the cross-transferability of SSR markers isolated from other bromeliad species to Tillandsia recurvata (L.) L. and T. aeranthos (Loisel.) Desf., epiphytes with great abundance in both natural and anthropogenic-modified environments, but with contrasting patterns of geographic distribution and mating systems. We tested a total of 27 microsatellite markers and successfully amplified seven polymorphic markers in T. recurvata and T. aeranthos. We then described cross-amplified markers in two populations per species, sampled in both anthropogenic-transformed and natural environments. T. recurvata presented lower allelic richness and heterozygosities, and greater inbreeding coefficient values. Such differences clearly reflect their contrasting mating systems (self-fertilizing in T. recurvata versus self-incompatible in T. aeranthus). The set of cross-amplified microsatellite markers described here will be a helpful tool to address a range of evolutionary and ecological questions.
Keywords: Cross-amplification; Epiphytes; Population genetics; SSR markers